Separation of nonfucosylated antibodies with immobilized FcγRIII receptors. (1st April 2013) - Bolton, Glen R.; Ackerman, Margaret E.; Boesch, Austin W.
<x xml:space="preserve">Abstract</x> Post‐translational modifications can dramatically impact protein activity, but identifying such structure:function relationships, as well as capitalizing on functionally enhanced variants, is a significant challenge. Here, affinity chromatography resins that contained immobilized FcγRIII receptors were used to enrich nonfucosylated antibodies 6‐ to 9‐fold, offering what may be a tractable method for both the identification of post‐translational modifications that affect function, as well as a means to enrich variants with enhanced activity. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:825–828, 2013